Dishevelled family proteins in serous ovarian carcinomas: a clinicopathologic and molecular study. Issue 3 (28th January 2020) - Karin‐Kujundzic, Valentina; Kardum, Vedran; Sola, Ida Marija; Paic, Frane; Skrtic, Anita; Skenderi, Faruk; Serman, Alan; Nikuseva‐Martic, Tamara; Vranic, Semir; Serman, Ljiljana
Abstract : Dishevelled family proteins (DVL1, DVL2, and DVL3) are cytoplasmic mediators involved in canonical and non‐canonical Wnt signaling that are important for embryonic development. Since Wnt signaling promotes cell proliferation and invasion, its increased activation is associated with cancer development as well. To get deeper insight into the behavior of Dishevelled proteins in cancer, we studied their expression in serous ovarian carcinomas [both low‐ (LGSC) and high‐grade (HGSC)], and HGSC cell lines OVCAR5, OVCAR8, and OVSAHO. DVL protein expression in serous ovarian carcinomas tissues was analyzed using immunohistochemistry, while DVL protein and mRNA expressions in HGSC cell lines were analyzed using Western blot and quantitative real‐time PCR. DVL1 protein expression was significantly higher in LGSC compared with normal ovarian tissue, while DVL3 was overexpressed in both LGSC and HGSC. DVL2 and DVL3 protein expression was higher in HGSC cell lines when compared with normal control cell line FNE1, while DVL1, DVL2, and DVL3 mRNA expression was significantly increased only in OVSAHO cell line. Survival analysis revealed no significant impact of DVL proteins on patients' outcome. Our data show an active involvement of Dishevelled family proteins in serous ovarian carcinomas. Further studies should confirm the clinical relevance of these observations.